Growth of bulk BiOBr single crystals for the characterization of intrinsic semi-conductive properties and application in ultraviolet photodetectors. Issue 28 (5th July 2022) - Zhang, Caiyun; Lin, Lingtong; Song, Jia; Lei, Longfei; Han, Liuyuan; Liu, Yuanyuan; Zhang, Jian; Zheng, Zhaoke; Wang, Zeyan; Wang, Peng; Cheng, Hefeng; Dai, Ying; et al.
Abstract : High-quality bulk BiOBr crystal with mm size is obtained by a space-confined chemical vapor transport strategy, & its intrinsic semi-conductive properties are characterized. It is fabricated into two-terminal UV photodetectors, which exhibit good UV detection performance. Abstract : Bismuth oxyhalides (BiOX, X = Cl, Br, and I) are commendable candidates for photocatalysis, photoelectric devices and so on, due to their unique characteristics, such as high ultraviolet (UV) absorption coefficient, high photoelectric conversion efficiency, favorable chemical stability, etc. However, the sizes of BiOX are limited to the micrometer level in the present studies and the intrinsic properties of BiOX are difficult to be accurately characterized due to the existence of the size effect, crystal defects and polycrystalline structure. Herein, BiOBr with a millimeter size (6 × 6 mm 2 ) is obtained by a modified space-confined chemical vapor transport (CVT) strategy. The intrinsic properties including physical and photoelectric properties are characterized using the obtained bulk sample with a clean surface. Moreover, it is fabricated into a two-terminal UV photodetector, which exhibits remarkable UV detection performance including good photoresponsivity ( R, 6.3 A W −1 ), detectivity ( D*, 3.2 × 10 9 Jones) and ultraviolet response time ( τ, 257 ms) at 334 nm. The successful preparation of the bulk single crystal paves the way for designing layered BiOBr for practical applications in UV photodetectors and even more possibilities.